2021
DOI: 10.5125/jkaoms.2021.47.6.432
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and management of mandibular fractures in a low-resource health facility in Ghana

Abstract: adherence to road safety regulation and poor road conditions are some of the major factors leading to MVA in developing countries like Ghana. Mandibular fracture, which can occur solitarily or in combination with other facial and skeletal injuries is also frequently caused by assault, industrial accidents, contact sports, falls, and firearm injuries.The Department of Oral and Maxillofacial Surgery at the Sunyani Regional Hospital, which has a bed capacity of 450, supports the medical needs of the middle, north… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Considering adults, the most frequent site was the symphysis/parasymphysis (36%), followed by the condyle (20%) and body (20%). However, in a recent study by Frimpong et al [37], the most frequent site in adults was parasymphysis (37.2%), followed by the body (26.8%) and the condyle (17.2%). According to this clinical analysis, there are no significant improvements to be made, while the simplification of the numerical model and the use of finite element simulation play an important role in the results.…”
Section: Discussionmentioning
confidence: 84%
“…Considering adults, the most frequent site was the symphysis/parasymphysis (36%), followed by the condyle (20%) and body (20%). However, in a recent study by Frimpong et al [37], the most frequent site in adults was parasymphysis (37.2%), followed by the body (26.8%) and the condyle (17.2%). According to this clinical analysis, there are no significant improvements to be made, while the simplification of the numerical model and the use of finite element simulation play an important role in the results.…”
Section: Discussionmentioning
confidence: 84%
“…and Adesina et al [ 36 ]. This may be related to the protruding nature of the mandible and its arch shape in the facial position [ 37 ]. The symphysial (682 cases, 36.16%) and condyle (656 cases, 34.78%) are also weak sites of the mandible and prone to fractures.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] Studies have shown that men are exposed to more maxillofacial trauma than women. 21,26,27 In another study conducted in Nigeria, it was stated that maxillofacial fractures are more common in women due to the fact that women have to work more in the external environment. 28 In our study, it was determined that the number of male was higher than female in all age groups, and this ratio was 2.5 / 1 in the total number of patients.…”
Section: Discussionmentioning
confidence: 99%